Supplier satisfaction with public sector competitive tendering processes. Issue 2 (10th June 2021) - Kelly, Stephen; Marshall, Donna; Walker, Helen; Israilidis, John
Abstract : Purpose: This paper aims to explore the supplier perspective on competitive tendering processes and build on an increasing and developing interest in supplier satisfaction with public sector procurement activities. Design/methodology/approach: Qualitative data was collected from 20 interviews with a variety of suppliers to the UK public sector, which was then analysed using Nvivo and a series of empirically supported propositions developed. Findings: The findings are combined into an integrated supplier satisfaction model, which explains how a multi-layered set of expectations (past and ideal) and quality dimensions (fairness, ambiguity, unnecessary information, tender focus, relationship irrelevance, unresponsiveness, outcome success) lead to dissatisfaction. This paper also establishes the implications of these judgments (non-response, poor quality and relationship impact) and that they are impacted by comparison to alternatives. Practical implications: Supplier dissatisfaction can have serious ramifications for public sector buying organisations by reducing the pool of applicants, creating relationship barriers and a disconnect between the tender and the eventual services provided. This paper gives empirically derived advice to managers and policymakers on how to avoid these issues. Social implications: Ensuring that as wide a pool of possible suppliers can respond to tender requests, means that the services that are provided by the public sector can make the most effective and efficient use of available resources. In addition, small to medium-sized enterprises may be encouraged to overcome their feelings of dissatisfaction and respond more frequently and readily to tender requests. Originality/value: This paper contributes to the field of public sector procurement and in particular that which looks at increasing supplier satisfaction, by developing a supplier satisfaction model based on supplier generated data, which uses disconfirmation theory to explain the dynamics of how individuals make judgments by comparing perceptions of performance with a multi-layered set of expectations. This paper identifies service quality dimensions that influence satisfaction judgments and the implications of these judgments.